Faktor yang Berhubungan dengan Pengetahuan Karyawan tentang Kesiapsiagaan Bencana Kebakaran di PT Trans Dana Profitri - Fahmi, Razi; Santi, Tahara Dilla; Arlianti, Nopa; Wardiati; Septiani, Riza (Jurnal EMT KITA, 2025)
Fire disaster preparedness is an important aspect in corporate risk management, especially in work environments that have the potential for fire. In 2023, there were 270 fire incidents in the Aceh region with residential fires dominating 103 incidents. The high number of fires indicates that public knowledge of fire prevention and control is still very minimal. This study aims to determine the factors related to employee knowledge of fire disaster preparedness at PT Trans Dana Profitri. This study is descriptive analytical with a cross-sectional approach. Data collection was carried out by interviews using questionnaires. The population in this study were all employees of PT Trans Dana Profitri at the Banda Aceh Representative Office and the sample was determined by the total population so that a sample of 50 employees was obtained. The study was conducted in December 2024. The statistical test used was the Chi Square Test (95%). The results of the study showed that employee knowledge about fire disaster preparedness was in the good category (74.0%), the age of employees was early adulthood (
Keywords: Age; Education; Information Source; Work Experience; Knowledge; Fire Disaster Preparedness